Regulating Exclusion from Financial Markets - BOND, PHILIP; KRISHNAMURTHY, ARVIND (Review of Economic Studies, 2004)
We study optimal enforcement in credit markets in which the only threat facing a defaulting borrower is restricted access to financial markets. We solve for the optimal level of exclusion, and link it to observed institutional arrangements. Regulation in this environment must accomplish two objectives. First, it must prevent borrowers from defaulting on one bank and transferring their resources to another bank. Second, and less obviously, it must give banks the incentive to make sizeable loans, and to honour their promises of future credit. We establish that the optimal regulation resembles observed laws governing default on debt. Moreover, if debtors have the right to a “fresh start” after bankruptcy then this must be balanced by enforceable provisions against fraudulent conveyance. Our optimal regulation is robust, in that it can be implemented in a way that does not require the regulator to have information about either the borrower or lender. Our results isolate the way in which specific institutions surrounding bankruptcy—namely rules governing asset garnishment and fraudulent conveyances—support loan markets in which borrowers have no collateral.